Two speakers are better than 5.1 [surround sound]. - Kraemer, A.
In this paper, the author outlines how a better grasp of how a brain interprets the ears' input led to virtual surround, in which two speakers sound like many more
Keywords: Dolby Digital 5.1.; Amplifiers; Brain; Multichannel virtualisers; Sound interpretation; Speakers; Virtual surround sound